TRAINING OF LIBRARY STAFF AND THEIR ACTIVITY - Rahmatullayeva Saodat Ibragimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the issue of librarian personnel in the republic during the years of independence. Also, the conditions created for the librarian personnel and the issues of their training are analyzed scientifically.